The Role of Facility Design in Preventing the Transmission of Healthcare-Associated Infections: Background and Conceptual Framework. (October 2013) - Zimring, Craig; Jacob, Jesse T.; Denham, Megan E.; Kamerow, Douglas B.; Hall, Kendall K.; Cowan, David Z.; Kasali, Altug; Lenfestey, Nancy F.; Do, Ellen; Steinberg, James P.
OBJECTIVE: To describe the conceptual framework and methodology used to conduct a comprehensive literature review of current evidence evaluating the role of the built environment in the transmission of healthcare-associated infections. BACKGROUND: A multidisciplinary approach to evaluating a vast and diverse dataset requires a conceptual framework to create a common understanding for interpretation. This common understanding is accomplished through the application of a "chain of transmission" model depicting temporal and physical paths of pathogens that cause healthcare-associated infections. The chain of transmission interventions model argues that infection can potentially be reduced by interrupting any of several links in the chain. TOPICAL HEADINGS: The key pathogens impacted by the built environment are identified. The chain of transmission and the conceptual framework are described. Opportunities for intervention through the built environment are presented, which in turn guide the subsequent methodology used to conduct the systematic literature review. CONCLUSIONS: The chain of transmission interventions model is a multidisciplinary conceptualization of the interaction between pathogens and the built environment, and this model facilitated a systematic literature review of a very large amount of data.